2013
DOI: 10.1103/physreve.87.042305
|View full text |Cite
|
Sign up to set email alerts
|

Decorrelation of the static and dynamic length scales in hard-sphere glass formers

Abstract: We show that, in the equilibrium phase of glass-forming hard-sphere fluids in three dimensions, the static length scales tentatively associated with the dynamical slowdown and the dynamical length characterizing spatial heterogeneities in the dynamics unambiguously decorrelate. The former grow at a much slower rate than the latter when density increases. This observation is valid for the dynamical range that is accessible to computer simulations, which roughly corresponds to that accessible in colloidal experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 73 publications
15
80
1
Order By: Relevance
“…with the correlation length diverging in the infinite pressure limit, and thus consistent with the ρ k = ρ j prediction 71 . Previous numerical investigations of the equation of state along the equilibrium metastable branch 60,65 for monodisperse hard sphere support the equation of state of Eq.…”
Section: Extended Theorysupporting
confidence: 84%
“…with the correlation length diverging in the infinite pressure limit, and thus consistent with the ρ k = ρ j prediction 71 . Previous numerical investigations of the equation of state along the equilibrium metastable branch 60,65 for monodisperse hard sphere support the equation of state of Eq.…”
Section: Extended Theorysupporting
confidence: 84%
“…The PTS correlation length is often described as a remedy to both problems, because it should be able to detect static correlations without a detailed knowledge of the local order involved in these correlations. In studies of binary mixtures of hard spheres, the PTS correlation length was shown to grow only modestly in the regime accessible to computer simulation (14,23), differently from the dynamical correlation length, which grows much more rapidly. These results suggested that no link exists between a single static length scale and the dynamical slowing down (the only exception would be close to a possible ideal glass transition temperature) (5,14).…”
Section: Significancementioning
confidence: 94%
“…It is intuitively defined as the average distance between pinned particles that forces the system to stay in an amorphous configuration with a vanishing configurational entropy. The reasons behind the popularity of PTS correlation lengths in the study of the glass transition are at least twofold: (i) they are expected to provide an "order-agnostic" method to measure static correlations (23,24); (ii) it is theoretically established that no divergence of the relaxation time of a glass at finite temperature can occur without the concomitant divergence of the static correlation length (25).…”
mentioning
confidence: 99%
“…While the lifetime of the heterogeneous dynamics is calculated using the three-time correlation functions, the length scale was not examined. In the present study, we further investigate the heterogeneous This phenomenon, typically called dynamic heterogeneity, has been investigated through diverse theoretical 6,10,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and experimental studies.…”
mentioning
confidence: 99%